STUDENTS’ PERCEPTION ON THE USE OF AUTHENTIC MATERIALS IN SENIOR HIGH SCHOOL - Firmansyah, Eka (Jurnal Pendidikan Bahasa dan Sastra, 2015)
AbstractThis study aims to find out the senior high school students’ perception on the use of materials (authentic and non-authentic) in the classroom. To select the representative sample, a sampling method was used. This research observes the perceptions of 10 first-grade students of a Senior High School on the use of authentic and non-authentic materials. They were taught using both materials, authentic and non-authentic. After that, to collect the data, they were asked to fill in the questionnaire (Likert Scale) which showed the students’ perception toward both materials, authentic and non-authentic. Then, the data were analyzed based on two different categories proposed by Peacock (1997) which covered: (1) overall class interest and enthusiasm and (2) self-reported interest enthusiasm. The result of the study indicated that authentic and non-authentic materials had their own benefit. The students indicated that the authentic materials slightly higher than the non-authentic ones.Keywords: EFL Methodology, english subject, materials (authentic and non-authentic).   AbstrakPenelitian ini bertujuan untuk menemukan persepsi para siswa terhadap penggunaan materi dalam pelajaran Bahasa Inggris (otentik dan non-otentik). Metode sampel digunakan untuk memilih sampel yang benar-benar mewakili keseluruhan populasi. Penelitian ini berupaya mengobservasi persepsi dari sepuluh siswa/siswi kelas X di sekolah menengah atas terhadap penggunaan materi pelajaran Bahasa Inggris yang berbentuk otentik dan non-otentik. Pada tahap proses pengumpulan data, para siswa/siswi mengisi angket (menggunakan skala Likert) yang menunjukkan persepsi mereka terhadap penggunaan bahan materi pelajaran Bahasa Inggris yang otentik dan non-otentik. Selanjutnya, data yang terkumpul dianalisis berdasarkan dua kategori dari Peacock (1997), yaitu: (1) antusiasme dan minat keseluruhan kelas. (2) antusiasme dan minat diri sendiri. Hasil dari penelitian ini menunjukkan bahwa masing-masing bentuk materi, baik otentik maupun nonotentik memberikan manfaat bagi siswa. Para siswa memberikan persepsi positif lebih tinggi terhadap penggunaan materi otentik dibandingkan dengan non-otentik.Kata-kata kunci:    Metodologi pengajaran bahasa Inggris,  materi otentik dan non-otentik